Code location based forwarding technique in opportunistic network - Halikul, Lenando; Qin, Feng; Mohamad Nazim, Jambli; Johari, Abdullah; Kartinah, Zen (IEEE, 2014)
In opportunistic network, the nodes have no knowledge regarding network topology. Hence, forwarding from the source node to the target destination node is a challenging issue. A connection between two nodes is unstable in opportunistic network, but the store-carry-forward scheme and node's mobility enable nodes to dissemination information between them. Flooding forward technique delivers message to every encounter node in transmission range. It incurs network congestion and consumes amount of network resources. This paper presents the location code-based data dissemination forward technique which utilizes the similarity between neighbor node's location code and the destination node's location code. The match degree approach is used to identify the relay node for a better way to disseminate data in opportunistic network. The experimental results show that code location approach delivers messages to the target destination with less overheads, and better performance as compared to flooding approach.